Bacillus amyloliquefaciens SC06 in the diet improves egg quality of hens by altering intestinal microbiota and the effect is diminished by antimicrobial peptide - Xu, Shujie; Wang, Fei; Zou, Peng; Li, Xiang; Jin, Qian; Wang, Qi; Wang, Baikui; Zhou, Yuanhao; Tang, Li; Yu, Dongyou; Li, Weifen (Frontiers in Nutrition, 2022)
This experiment investigated the effects of B. amyloliquefaciens SC06 (BaSC06) and its combination with antimicrobial peptide (AMP) on the laying performance, egg quality, intestinal physical barrier, antioxidative status and immunity of commercial Jingbai strain laying hens. A total of 270 202-d-old laying hens were assigned into 3 treatments with 6 replicates per treatment (15 birds per replicate): (1) basal diet (Control), (2) basal diet with B. amyloliquefaciens SC06(5×10^8 CFU/kg), (3) basal diet with 100mg/ kg AMP and B. amyloliquefaciens SC06(5×10^8 CFU/kg), for an experimental duration of 35 d. The results showed that BaSC06 significantly improved laying performance and egg quality of laying hens. However, there was a tendency to increase laying performance and decrease egg quality for the addition of AMP compared to the BaSC06 group. Also, both BaSC06 and its combination with AMP treatment increased length of microvilli and the content of tight junction protein in jejunum, and BaSC06 combination with AMP treatment is better than BaSC06 treatment alone. Compared to control, most of the serum antioxidant enzyme activities were significantly increased in the BaSC06+AMP group, the BaSC06 group only increased the activity of GSH-Px. Microbiota analysis showed that BaSC06 increased the absolute abundance of the butyrate-producing gut bacteria Ruminococaaoeae UCG-005, while the addition of AMP reduced the number of microorganisms detected and weakened the effect of BaSC06. BaSC06 acts as an anti-inflammatory agent by regulating the gut microbiota, and AMP further attenuates the immune response by reducing the number of gut microbes based on improved intestinal microbiota composition.